2005
DOI: 10.1002/jnr.20563
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neuronal protein 22 expression and cytoskeletal association in the alcohol‐dependent and withdrawn rat brain

Abstract: The action of alcohol on neuronal pathways has been an issue of increasing research focus, with numerous findings contradicting the previously accepted idea that its effect is nonspecific. The human NP22 (hNP22) gene was revealed by its elevated expression in the frontal cortex of the human alcoholic. The sequences of hNP22 and the rat orthologue rNP22 contain a number of domains consistent with those of cytoskeletal-interacting proteins. Localization of rNP22 is restricted to the cytoplasm and processes of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
(47 reference statements)
1
10
0
4
Order By: Relevance
“…, 2005). NP22 colocalizes with all three major components of neuronal microtubules, tau, α‐tubulin and MAP2 (Depaz et al. , 2005), and with F‐actin (Depaz et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2005). NP22 colocalizes with all three major components of neuronal microtubules, tau, α‐tubulin and MAP2 (Depaz et al. , 2005), and with F‐actin (Depaz et al.…”
Section: Discussionmentioning
confidence: 99%
“…NP22 colocalizes with all three major components of neuronal microtubules, tau, α‐tubulin and MAP2 (Depaz et al. , 2005), and with F‐actin (Depaz et al. , 2005), which is highly expressed in dendrites, synapses, dendritic spines and postsynaptic densities (Markham & Fifkova, 1986; Fifkova & Morales, 1992; Adam & Matus, 1996; Halpain, 2000) .…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study using rat brain has demonstrated that phosphorylation of microtubule-associated proteins, which modulate the functional properties of microtubules, is altered by ethanol exposure [93]. A study using hepatoma-derived cells has shown altered integrity of proteins associated with microtubules following ethanol exposure [94].Altered expression of neuronal protein 22, which interacts with microfilament and microtubule matrices, may also be involved in the pathogenesis of alcoholic neuropathy [95]. Thus, defects in axonal transport and cytoskeletal properties of axons may be one of the important pathways involved in alcohol induced peripheral neuropathy.…”
Section: Effects On Axonal Transport and Cytoskeletal Propertiesmentioning
confidence: 99%
“…These genes are basically co-dominant in classes 5 and 3, representing pulmonary carcinoids (COID) and small cell lung cancer (SCLC), respectively. TAGLN3 associates with and regulates F-actin, α-tubulin, tau and MAP2 [50]. CRMP1 is a phosphoprotein and controls microtubules [51].…”
Section: Resultsmentioning
confidence: 99%